2011
DOI: 10.1051/limn/2011019
|View full text |Cite
|
Sign up to set email alerts
|

Ecological informatics approach to screening of integrity metrics based on benthic macroinvertebrates in streams

Abstract: -Benthic macroinvertebrates are considered as a representative taxon that indicates the ecological status of freshwater ecosystems. Numerous indices derived from community data have been proposed to estimate either biological water quality or ecosystem health. In this study, metrics based on benthic macroinvertebrates at the family level were screened using ecological informatics to provide a multi-metric measurement that would be suitable for presenting ecological integrity across different levels of environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…It is being conducted in five main river basins, where 640-960 sites are selected for surveying diatoms, macroinvertebrates, and fish two times per year. Multitaxa community organization and water quality according to the Korean Saprobic Index (Bae et al 2011;Cho et al 2011;Jun et al 2012) are reported based on survey results. In this review, we analyze the NAEMP, which focus specifically on assessing the ecological health of South Korean streams.…”
Section: Biomonitoring Program Objectives and Brief Historymentioning
confidence: 99%
See 2 more Smart Citations
“…It is being conducted in five main river basins, where 640-960 sites are selected for surveying diatoms, macroinvertebrates, and fish two times per year. Multitaxa community organization and water quality according to the Korean Saprobic Index (Bae et al 2011;Cho et al 2011;Jun et al 2012) are reported based on survey results. In this review, we analyze the NAEMP, which focus specifically on assessing the ecological health of South Korean streams.…”
Section: Biomonitoring Program Objectives and Brief Historymentioning
confidence: 99%
“…Multimetric approaches for benthic macroinvertebrates are the most widely used approach for waterquality assessments (Bonada et al 2006). Large-scale multimetric indices have been developed for macroinvertebrates in many countries and continents (Klemm et al 2003;Hering et al 2006;Baptista et al 2007;Stoddard et al 2008;Moya et al 2011;Cho et al 2011;Jun et al 2012). The USEPA-NRSA uses both multimetric and O/E indices for assessing all wadeable streams in the conterminous USA Stoddard et al 2008;USEPA 2013).…”
Section: Approaches To Biological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These communities are significant indicators of ecological status of a range of water habitats and changes in abundance and diversity can be considered as a response to variations in water quality and might reflect modifications produced in freshwater food webs (Abrantes et al, 2009;Cho et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological health assessment and restoration are important topics in this special issue. Cho et al (2011) consider the various metrics used to monitor benthic macroinvertebrates, in terms of stream biological water quality and ecosystem health, and test their utility in comparison with conventional indicators. J.H.…”
mentioning
confidence: 99%